2002
DOI: 10.1016/s0300-483x(02)00190-7
|View full text |Cite
|
Sign up to set email alerts
|

Trimellitic anhydride (TMA) dust induces airway obstruction and eosinophilia in non-sensitized guinea pigs

Abstract: Trimellitic anhydride (TMA) causes asthma after a latency period of sensitization. In non-sensitized humans and animals, limited studies indicate that TMA exposure may also cause symptoms of asthma without a latency period. Our previous studies (J. Pharmacol. Exp. Ther. 296 (2001) 284) in a guinea pig model of TMA-induced asthma demonstrated that sensitization and the complement system were required for eosinophilia. TMA conjugated to guinea pig serum albumin (TMA-GPSA) was used to elicit the response. Since o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…To verify that HDM challenge induces allergic activation of mast cells, we quantified the levels of HDM‐specific immunoglobulins following the first challenge and found that HDM‐treated guinea pigs were indeed sensitized to the allergen as shown by increased levels of HDM‐specific IgG 1 and IgG 2 compared with PBS‐treated guinea pigs. The induction of both IgG subclasses in response to allergens, including dust mites, has previously been described in guinea pigs 18,22‐24 . Furthermore, it has been shown that both immunoglobulins can induce the ASM contraction, 22,25 also in line with our study.…”
Section: Discussionsupporting
confidence: 91%
“…To verify that HDM challenge induces allergic activation of mast cells, we quantified the levels of HDM‐specific immunoglobulins following the first challenge and found that HDM‐treated guinea pigs were indeed sensitized to the allergen as shown by increased levels of HDM‐specific IgG 1 and IgG 2 compared with PBS‐treated guinea pigs. The induction of both IgG subclasses in response to allergens, including dust mites, has previously been described in guinea pigs 18,22‐24 . Furthermore, it has been shown that both immunoglobulins can induce the ASM contraction, 22,25 also in line with our study.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study revealed that TMA elicits significant airway obstruction and eosinophilia in a non-sensitized animal, and with even greater airway obstruction occurring in a sensitized animal [16] . Using animal model, it is shown that TMA induced typical morphological changes of the inflamed skin, strong infiltration with T cells, major histocompatibility complex positive cells, eosinophils, and mast cells, a T-helper cell-type 2 cytokine profile and strong increase of serum IgE levels [17] .…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, this is for the first time to report disturbed respiration induced in mice during and after challenge with free TMA dust. As an alternative route to inhalation exposure at challenge, intranasal or intratracheal instillation of chemicals has also been employed (Ebino et al, 1998;Scheerens et al, 1999;Regal et al, 2001;Herrick et al, 2002;Larsen and Regal, 2002;Sailstad et al, 2003;Farraj et al, 2004;Vanoirbeek et al, 2004). There are, however, some limitations to real-time monitoring of physiological respiration patterns when using these methods.…”
Section: Discussionmentioning
confidence: 96%
“…Under these circumstances, since 1994, the Mouse IgE Test (MIGET; Kimber et al, 1996) and the Guinea Pig Test (GPT; Karol, 1983;Hayes et al, 1992;Larsen and Regal, 2002) have been recognized and recommended as the major airway sensitization tests by the European Center for Ecotoxicology and 98 UEDA ET AL.…”
Section: Introductionmentioning
confidence: 99%